The Influence Of Entrepreneurial Ability And Knowledge On The Success Of Micro, Small And Medium Enterprises (Msmes) In Bengkulu City - Dona, Hesti Pestiko; Soleh , Ahmad; Nasution , Suswati (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
Entrepreneurship plays an important role in improving economic independence through the development of Micro, Small, and Medium Enterprises (MSMEs). The success of MSMEs in Bengkulu City is strongly influenced by the entrepreneurial capability and entrepreneurial knowledge of business actors. The ability to manage, innovate, and make appropriate decisions, supported by knowledge of business strategies and opportunities, are key factors in enhancing competitiveness and business success. The purpose of this study is to identify and analyze the influence of entrepreneurial capability and entrepreneurial knowledge on the success of Micro, Small, and Medium Enterprises (MSMEs), both partially and simultaneously. The research method used is a quantitative approach with a descriptive design. The research sample consisted of 100 respondents selected using a purposive sampling technique. Data analysis was conducted through validity tests, reliability tests, multiple Entrepreneurship plays an important role in improving economic independence through the development of Micro, Small, and Medium Enterprises (MSMEs). The success of MSMEs in Bengkulu City is strongly influenced by the entrepreneurial capability and entrepreneurial knowledge of business actors. The ability to manage, innovate, and make appropriate decisions, supported by knowledge of business strategies and opportunities, are key factors in enhancing competitiveness and business success. The purpose of this study is to identify and analyze the influence of entrepreneurial capability and entrepreneurial knowledge on the success of Micro, Small, and Medium Enterprises (MSMEs), both partially and simultaneously. The research method used is a quantitative approach with a descriptive design. The research sample consisted of 100 respondents selected using a purposive sampling technique. Data analysis was conducted through validity tests, reliability tests, multiple